2011
DOI: 10.1002/cssc.201000299
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Solubilization and Aqueous Phase Reforming for the Production of Aromatic Chemicals and Hydrogen

Abstract: The solubilization and aqueous phase reforming of lignin, including kraft, soda, and alcell lignin along with sugarcane bagasse, at low temperatures (T≤498 K) and pressures (P≤29 bar) is reported for the first time for the production of aromatic chemicals and hydrogen. Analysis of lignin model compounds and the distribution of products obtained during the lignin aqueous phase reforming revealed that lignin was depolymerized through disruption of the abundant β-O-4 linkages and, to a lesser extent, the 5-5' car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(105 citation statements)
references
References 26 publications
2
100
0
3
Order By: Relevance
“…(characteristic of crystallised cellulose), indicated that the amorphous area of the cellulosic component was more affected by the alkaline peroxide treatment, showing the ease of crystallinity during hydrolysis, as also observed by XRD result (Zakzeski and Weckhuysen 2011). Also, the slightly shift band at 1160 to 1164 cm −1 (Fig.…”
Section: Correlation Between Fourier Transform Infrared Spectroscopy supporting
confidence: 69%
“…(characteristic of crystallised cellulose), indicated that the amorphous area of the cellulosic component was more affected by the alkaline peroxide treatment, showing the ease of crystallinity during hydrolysis, as also observed by XRD result (Zakzeski and Weckhuysen 2011). Also, the slightly shift band at 1160 to 1164 cm −1 (Fig.…”
Section: Correlation Between Fourier Transform Infrared Spectroscopy supporting
confidence: 69%
“…However,the complete dissolution of an (initially insoluble) Organosolv lignin at 115-130 8 8Cu nder neutral aqueous conditions was demonstrated in ap ressure vessel equipped with ag lass window (Figure 10 a). [375] By contrast, dissolution of aK raft lignin (Figure 10 b) was accompanied by agglomeration of solids onto the window.Gas bubbles were observed from the agglomerates,s uggesting formation of gaseous products.I n a1:1 water:ethanol mixture,both Kraft and Organosolv lignin were fully dissolved at 115 8 8Ca nd agglomeration was completely suppressed. [372] Figure 9.…”
Section: Solventsmentioning
confidence: 95%
“…[375] Lignin solubility is influenced, at least in part, by the structure,b onding properties and functional group density of the macromolecules.Atroom temperature,isolated lignins that closely resemble native lignins (e.g.,cellulolytic enzyme lignins,certain Organosolv lignins) have low water solubility, and low solubility in pure polar organic solvents (e.g., ethanol, acetone,1 ,4-dioxane), but moderate solubility in alkaline solutions,and may be completely soluble in mixtures of polar organic solvents and water that have the right solvent factor-9:1a cetone:water and 96:4 dioxane water are established examples.Bycontrast, technical lignins (e.g., Kraft lignin) are often comparatively insoluble in the same organic solvents or their mixtures with water. [372] Selected classes of imidazoliumderived ionic liquids (ILs) have shown capability for dissolving both lignin and lignocellulosic biomass itself (in sawdust form), [376][377][378][379] in particular those with strongly hydrogenbonding basic anions to disrupt hydrogen bonding networks.…”
Section: Solventsmentioning
confidence: 99%
“…Though this has not been confirmed by any studies using model compounds. To our knowledge, this is one of the first reports on the cleavage of 5-5′ linkage in the phenolic lignin model compound 6, proved by the formation of methylguaiacol (7%) and guaiacol (12%) [86].…”
Section: Reductive C-c Bond Cleavagementioning
confidence: 71%